Quitting patient care and career break intentions among general practitioners in South West England: findings of a census survey of general practitioners. Issue 4 (11th April 2017) - Fletcher, Emily; Abel, Gary A; Anderson, Rob; Richards, Suzanne H; Salisbury, Chris; Dean, Sarah Gerard; Sansom, Anna; Warren, Fiona C; Campbell, John L
Abstract : Objective: Given recent concerns regarding general practitioner (GP) workforce capacity, we aimed to describe GPs' career intentions, especially those which might impact on GP workforce availability over the next 5 years. Design: Census survey, conducted between April and June 2016 using postal and online responses, of all GPs on the National Health Service performers list and eligible to practise in primary care. Two reminders were used as necessary. Setting: South West England (population 3.5  million), a region with low overall socioeconomic deprivation. Participants: Eligible GPs were 2248 out of 3370 (67 % response rate). Main outcome measures: Reported likelihood of permanently leaving or reducing hours spent in direct patient care or of taking a career break within the next 5 years and present morale weighted for non-response. Results: Responders included 217 7 GPs engaged in patient care. Of these, 863 (37% weighted, 95%  CI 35 % to 39 %) reported a high likelihood of quitting direct patient care within the next 5 years. Overall, 1535 (70% weighted, 95%  CI 68 % to 72 %) respondents reported a career intention that would negatively impact GP workforce capacity over the next 5 years, through permanently leaving or reducing hours spent in direct patient care, or through taking a career break. GP age was an important predictor of career intentions; sharp increases in the proportion of GPs intending to quit patient care were evident from 52 years. Only 305 (14% weighted, 95%  CI 13 % to 16 %) reported high morale, while 1195 ( 54 % weighted, 95%  CI 52 % to 56 %) reported low morale. Low morale was particularly common among GP partners. Current morale strongly predicted GPs' career intentions; those with very low morale were particularly likely to report intentions to quit patient care or to take a career break. Conclusions: A substantial majority of GPs in South West England report low morale. Many are considering career intentions which, if implemented, would adversely impact GP workforce capacity within a short time period. Study registration: NIHR HS&DR - 14/196/02, UKCRN ID 20700.